Human Resource Development: Approaches to Organization Success - sanamthong, ekkasit (KASEM BUNDIT JOURNAL, 2019)
Main approaches of human resource development can be summarized as follows: individual development, career development, organizational development, and performance management. Human resource development process consists of the analysis of the needs for human resource development, the design of methodology(ies) and selection of appropriate tool(s) to be utilized in human resource development, implementation of human resource development plan(s), and assessing and evaluation of human resource development plan(s). The appropriate development of each individual personnel to optimize their potentials could be done by improving knowledge base, creating an understanding, improving the skill(s), creating positive attitude and changing of behavior, all of which are critical drivers to elevate the organization to sustainable growth and success.